1987
DOI: 10.1111/j.1365-2044.1987.tb04119.x
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal nitroglycerine attenuates pressor response to tracheal intubation in beta‐blocker treated hypertensive patients

Abstract: Key wordsAnu (,v[iit,tir t~c h n i y u~.~: tracheal intubation Phurmucolugy: nitroglycerine.Tachycardia and hypertension are well-documented reflex cardiovascular effects of laryngoscopy and tracheal intubation in normotensive subjects.' The extent of these reflexes is more marked in both treated and untreated hypertensive patients.2 Intranasal nitroglycerine has been shown to attenuate the pressor response to laryngoscopy and intubation in normotensive p a t~e n t s .~ Its use in hypertensive patients has no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Previous studies[ 11 17 18 19 20 ] have also documented that NTG does not attenuate the rise in HR after intubation which can be attributed to reflex tachycardia produced by vasodilation.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies[ 11 17 18 19 20 ] have also documented that NTG does not attenuate the rise in HR after intubation which can be attributed to reflex tachycardia produced by vasodilation.…”
Section: Discussionmentioning
confidence: 95%
“…NTG had been administered in different doses and through different approaches like intranasal, topically or parenterally as a bolus or infusion to attenuate hemodynamic responses during laryngoscopy and intubation. 19 Kumari I et al used sublingual Nitroglycerin in two doses (0.4mg and 0.8mg) Kamra S et al used 2% topical Nitroglycerin ointment equivalent to 30 mg Nitroglycerin. 13,14 Fassoulaki A and Kaniaris P used Nitroglycerin intranasally in a dose of 60 mg. 15 Anant and Waghray used intranasal NTG spray for attenuation of pressor response to intubation.…”
Section: Discussionmentioning
confidence: 99%
“…also found similar results coinciding our study. 13,14,17,19,23 Fusciardi J et al concluded that addition of Nitroglycerin by infusion to low-dose Fentanyl anesthesia produced no significant change in MPB, heart rate, cardiac index, or PCWP and is an attractive method for induction as well as decreasing the incidence of myocardial ischemia associated with laryngoscopy and intubation in patients with stable angina undergoing short-duration noncardiac surgery.…”
Section: Mean Blood Pressurementioning
confidence: 99%
See 1 more Smart Citation
“…Nitroglycerine (NTG) is effective when administered nasally in a dose of 0.75 mg and given 60 sec CANADIAN JOURNAL OF ANAESTHESIA before intubation. 163 The safety of this route of administration is apparent from a similar study which showed efficacy without side effects and involved the use of a dose of 60 mg of NTG, fully 80 times larger than the former study's dose. 164 Prophylactic infusions of NTG in cardiac surgical patients have been shown to decrease hypertensive responses to intubation, its The effectiveness of NTG has been questioned when given intravenously in noncardiac patients.…”
Section: Coronary Artery Diseasementioning
confidence: 99%